ANALISIS KEKUATAN MEKANIK SERAT KELAPA BERMATRIK UNSATURATED POLYESTER DENGAN VARIASI LAMANYA WAKTU PERLAKUAN ALKALI NaOH DAN KOH - Muhammad Fauzan Nurhidayat; Sri Hastuti; Faiz Listyanda (ELEMEN : JURNAL TEKNIK MESIN, 2026)
Composite materials have received attention from automotive industry players. An interesting raw material to be developed is coconut fiber waste which is abundant in Indonesia as a tropical country. The study aims to analyze the mechanical strength of coconut fiber-unsaturated polyester BQTN-EX 157 composite with volume fraction of 30%: 70%, fabricated using hand lay-up method of random fiber orientation with 15mm fiber length. This study has three variations of alkalization treatment length; 4 hours, 6 hours, and 8 hours treatment. Alkalization uses 5% NaOH and 5% KOH solutions. The tests used ASTM D6110 charpy impact test and ASTM D638 tensile test. The 6-hour KOH immersion treatment had the highest absorption energy of 4.9085 Joules and the 4-hour KOH immersion treatment had the highest impact price of 0.052 J/mm2. The 6-hour KOH immersion treatment received a tensile stress value of 13.60 MPa with the highest elastic modulus of 852.79 MPa. Observation of specimen fracture shows the presence of fiber pullout, voids, brittle fracture, rich matrix and others.